Cardiovascular, respiratory, electrolyte and acid–base balance during continuous dexmedetomidine infusion in anesthetized dogs. (15th April 2013) - Congdon, Jonathan M; Marquez, Megan; Niyom, Sirirat; Boscan, Pedro
Abstract: Objective: To evaluate the cardiovascular, respiratory, electrolyte and acid‐base effects of a continuous infusion of dexmedetomidine during propofol‐isoflurane anesthesia following premedication with dexmedetomidine. Study design: Prospective experimental study. Animals: Five adult male Walker Hound dogs 1–2 years of age averaging 25.4 ± 3.6 kg. Methods: Dogs were sedated with dexmedetomidine 10 μg kg −1 IM, 78 ± 2.3 minutes (mean ± SD) before general anesthesia. Anesthesia was induced with propofol (2.5 ± 0.5 mg kg −1 ) IV and maintained with 1.5% isoflurane. Thirty minutes later dexmedetomidine 0.5 μg kg −1 IV was administered over 5 minutes followed by an infusion of 0.5 μg kg −1 hour −1 . Cardiac output (CO), heart rate (HR), ECG, direct blood pressure, body temperature, respiratory parameters, acid‐base and arterial blood gases and electrolytes were measured 30 and 60 minutes after the infusion started. Data were analyzed via multiple linear regression modeling of individual variables over time, compared to anesthetized baseline values. Data are presented as mean ± SD. Results: No statistical difference from baseline for any parameter was measured at any time point. Baseline CO, HR and mean arterial blood pressure (MAP) before infusion were 3.11 ± 0.9 L minute −1, 78 ± 18 beats minute −1 and 96 ± 10 mmHg, respectively. During infusion CO, HR and MAP were 3.20 ± 0.83 L minute −1, 78 ± 14 beats minute −1 and 89 ± 16 mmHg, respectively. No differences were found in respiratory rates, PaO2, PaCO2, pH, base excess, bicarbonate, sodium, potassium, chloride, calcium or lactate measurements before or during infusion. Conclusions and clinical relevance: Dexmedetomidine infusion using a loading dose of 0.5 μg kg −1 IV followed by a constant rate infusion of 0.5 μg kg −1 hour −1 does not cause any significant changes beyond those associated with an IM premedication dose of 10 μg kg −1, in propofol‐isoflurane anesthetized dogs. IM dexmedetomidine given 108 ± 2 minutes before onset of infusion showed typical significant effects on cardiovascular parameters.